Explaining incumbent re-election in authoritarian elections: evidence from a Chinese county. Issue 7 (3rd October 2018) - Luo, Ting
ABSTRACT: Despite the burgeoning comparative literature on authoritarian elections, less is known about the dynamics of competition in authoritarian subnational elections where opposition is not allowed to organize into parties. Local elections without partisan competition in single-party authoritarian regimes provide considerable advantages to the incumbents and may well turn the incumbent advantage common in liberal democracies into incumbent dominance. What economic factors can break incumbent dominance in such competition without parties? With quantitative and qualitative evidence from grassroots elections in China, this article illustrates that economic growth and industrial economic structure offering more economic autonomy help to break incumbent dominance and increase the prospects of successful challenge to incumbency by non-party outsiders. The examination of the findings in a broad context in China and against the backdrop of local democratization in the developing world suggests that though we may observe successful challenge to incumbency, liberalization of the political system requires not only competition, but also a relatively autonomous economy to sustain liberalization prospects. The findings contribute to the literature on electoral authoritarianism, subnational democratization and China's grassroots elections.